Efficacy of Shampoo Made from Bangle Rhizome Extract (Zingiber montanum) Against Head Lice (Pediculus humanus capitis) - Susilowati, Rina Priastini; Sari, Monica Puspa; Santoso, Adit Widodo (Indonesian Journal of Tropical and Infectious Disease, 2024)
Head lice is a major public health problem worldwide. Its treatment is challenging due to product failures resulting from rapidly emerging resistance to existing treatments, incorrect treatment application, and misdiagnosis. Various head lice treatments with different mechanisms of action have been developed and explored over the years, with limited reports on systematic assessments of their efficacy and safety. The head lice shampoo currently in circulation is 1% permethrin-based. Side effects of using permethrin-based shampoos include skin irritation and high resistance. The research conducted aims to present strong evidence that the use of shampoo made from bangle rhizome extract against head lice mortality is safer to use. The study used 240 head lice taken from elementary school students aged 8-12 years in a school in Bekasi. The study group was divided into 6 groups: negative control group (using baby shampoo), positive control group (using permethrin-based anti-lice shampoo), shampoo treatment group made from bangle rhizome extract with dose of 0.5%, 1%, 2% and 4%. In addition to calculating the number of head lice deaths per group, the time of death was also calculated to determine LC50 (Lethal Concentration 50), LC90 (Lethal Concentration 90), LT50 (Lethal Time 50), and LT90 (Lethal Time 90). The results showed a highly significant difference between the number of head lice deaths in the control group and the shampoo treatment group made from bangle rhizome extract (p<0.01). Likewise, there was a highly significant difference for the time of death of head lice in the control group and the shampoo treatment group made from bangle rhizome extract. Statistical analysis showed LC50 of 0.96%, LC90 of 2.84%, LT50 of 57.72 minutes, and LT90 of 28.79 minutes. It can be concluded that the effective dose of shampoo made from bangle rhizome extract is 4%, which can kill 100% of head lice within 27 minutes.